2018
DOI: 10.1186/s12875-018-0758-x
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional investigation of the health needs of asylum seekers in a refugee clinic in Germany

Abstract: BackgroundOver one million asylum seekers were registered in Germany in 2016, most from Syria and Afghanistan. The Refugee Convention guarantees access to healthcare, however delivery mechanisms remain heterogeneous. There is an urgent need for more data describing the health conditions of asylum seekers to guide best practices for healthcare delivery. In this study, we describe the state of health of asylum seekers presenting to a multi-specialty primary care refugee clinic.MethodsDemographic and medical diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 9 publications
1
44
0
2
Order By: Relevance
“…To our knowledge no other studies report lifetime prevalence of ill health among asylum seekers and refugees, nor among the general Syrian population. Studies of point prevalence among asylum seekers and refugees commonly report headache, injuries, and musculoskeletal, dermatological, dental, respiratory, gastrointestinal, and mental health problems to be frequent problems [13,[28][29][30][31]. Most of these studies evaluate clinic-based populations and rely on retrospective assessments of clinical records, making it impossible to extrapolate prevalence proportion to the population level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge no other studies report lifetime prevalence of ill health among asylum seekers and refugees, nor among the general Syrian population. Studies of point prevalence among asylum seekers and refugees commonly report headache, injuries, and musculoskeletal, dermatological, dental, respiratory, gastrointestinal, and mental health problems to be frequent problems [13,[28][29][30][31]. Most of these studies evaluate clinic-based populations and rely on retrospective assessments of clinical records, making it impossible to extrapolate prevalence proportion to the population level.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence proportions standardised to the age and gender distribution of the total Syrian population in Norway by the end of 2017 [6] Overall, 30% (27-33) reported chronic pain (Table 2), while the percentages of chronic pain were 46% (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) among those reporting headaches, and 57% (48-64) among those reporting musculoskeletal pain. The prevalence of long-term illness or injury, lasting for more than one year and affecting daily life was 29% (26)(27)(28)(29)(30)(31)(32)(33). The items measuring mental health showed satisfying internal consistency (Cronbach's alfa for HSCL-10: 0.89 and for HTQ: 0.92).…”
Section: Health Status and Use Of Medicationmentioning
confidence: 99%
“…Although trauma constitute one of the major events faced by refugee population, however the less number of published studies and inadequate data collection largely restricts the detail information regarding injury patterns. 20,21 The trauma can range from physical and emotional to social traumatic events resulting in impairment in physical or emotional functions. [22][23][24] The exact details of the injuries may not be available and additionally the injuries may be recorded as unspecified.…”
Section: Injury Distributionmentioning
confidence: 99%
“…[22][23][24] The exact details of the injuries may not be available and additionally the injuries may be recorded as unspecified. 21 In one study the patients presented with the complaint suggestive of head injury, fractures, skin injuries and burn injuries. 20,25 The common cause of head injury was assault however, the motor vehicle accidents were less prevalent (probably due to limited access in refugee camps).…”
Section: Injury Distributionmentioning
confidence: 99%
“…These observations led to claims for a more integrated and more individualized health care provision for refugees in Europe [ 7 ]. However, we noted that most studies that investigated healthcare in refugee camps had a cross-sectional approach and evaluated the prevalence of specific health conditions (e.g., psychiatric conditions or communicable diseases) or focused on selected populations such as unaccompanied minors [ 8 14 ]. We concluded that more knowledge is needed on the provision of continuous primary care for asylum seekers since continuous care is considered an important contributor to quality-of-care and patient satisfaction [ 15 , 16 ] .…”
Section: Introductionmentioning
confidence: 99%